Biotemplated Synthesis of Titanium Oxide Nanoparticles in the Presence of Root Extract of Kniphofia schemperi and Its Application for Dye Sensitized Solar Cells. (20th February 2021) - Bekele, Eneyew Tilahun; Zereffa, Enyew Amare; Gultom, Noto Susanto; Kuo, Dong-Hau; Gonfa, Bedasa Abdisa; Sabir, Fedlu Kedir
Abstract : Metal oxide nanoparticles prepared by biological route using green plant parts as a template are eco-friendly as well as yield good results than the conventional methods. This present study focusses on biosynthesis and characterization of TiO2 NPs using root extract of Kniphofia schemperi for dye-sensitized solar cells. TiO2 NPs were synthesized using 0.25 M titanium tetra butoxide in the presence of root extract of Kniphofia schemperi with the volume ratios. The analysis result revealed that the synthesized TiO2 NPs were thermally stable above 500°C and have spherical morphology, with the average crystalline size of 11.7, 8.3, and 8.6 nm, and band gap energy of 3.35 eV, 3.33 eV, and 3.36 eV, respectively, for the TiO2 NPs prepared at the volume ratios of 2 : 3, 1 : 1, and 3 : 2. Biosynthesized TiO2 NPs were used as photoanode in dye-sensitized solar cells (a device used for converting absorbed light into electricity). Solar cell devices were fabricated using roots of Kniphofia schemperi sensitizer in the presence of TiO2 NPs biosynthesized within (2 : 3, 1 : 1, and 3 : 2) volume ratio, which showed power conversion efficiency of 0.039%, 0.117%, and 1.3%. Incident photon to current conversion efficiency (IPCE) analysis using TiO2 (2 : 3, 1 : 1, and 3 : 2) photoelectrodes showed 6.64%, 2.66%, and 18%. Among the biosynthesized TiO2 different volume ratios, TiO2 (3 : 2) NPs showed relatively maximum solar cell efficiency and IPCE value due to its uniform spherical shape that enables to absorb large dye molecules on its surface, and this intern improves device efficiency.